Pengenalan Rumah Sehat Pada Murid Taman Kanak-Kanak TK Dua Putra Sudiang : id - Andi Abidah; Noor Fadilah Romadhani; Tri Amartha Wiranata; Azrah Aeni (V-MACHINE: Vocational and Mechanical Community Service Journal, 2024)
Childhood is a golden period in the formation of healthy living habits. Therefore, children need to be introduced to the concept of a healthy home from an early age. The targets for this PKM are kindergarten students at Kindergarten Dua Putra Sudiang, Makassar City. The aim of this PKM activity is to introduce healthy homes to kindergarten students at TK 2 Putra Sudiang where this can support students in creating healthy and comfortable home environmental conditions. The implementation method used is the method of discussion, question and answer and direct practice in recognizing the difference between a healthy house and an unhealthy house through simple activities. It is hoped that this PKM activity will be able to increase partners' knowledge about healthy homes. Based on the results of the training, it can be concluded that 1) partners can understand a healthy house, and 2) partners can know the difference between a public house and a healthy house, and 3) partners can explain the activities of arranging a house into a healthy home through children understanding simple actions in maintaining cleanliness such as cleaning toys, throwing rubbish in its place, wiping the table, holding a broom properly, and washing hands before and after eating.